Spatially Explicit Assessment of Sandhill Crane Exposure to Potential Transmission Line Collision Risk. Issue 7 (20th July 2021) - Hays, Quentin R.; Tredennick, Andrew T.; Carlisle, Jason D.; Collins, Daniel P.; Carleton, Scott A.
ABSTRACT: Infrastructure development can affect avian populations through direct collision mortality. Estimating the exposure of local bird populations to the risk of direct mortality from infrastructure development requires site‐ and species‐specific data, which managers may find difficult to obtain at the scale over which management decisions are made. We quantify the potential exposure of sandhill cranes ( Antigone canadensis ) to collision with horizontal structures (e.g., transmission lines) within vital wintering grounds of the Middle Rio Grande Valley (MRGV), New Mexico, USA, 2014–2020. Limited maneuverability and visual acuity make sandhill cranes vulnerable to collisions with infrastructure bisecting their flight paths. We used data from 81 global positioning system (GPS)‐tagged cranes to estimate the spatially explicit flight height distribution along the MRGV, the passage rate across hypothetical transmission lines, and the resulting exposure rate (exposed passes/crane/day). The exposure rate ranged from 0–0.28 exposed passes/crane/day (median = 0.015) assuming an exposure zone of 7–60 m above ground level, and identified hotspots of potential exposure within the MRGV. Mapped exposure rates can assist in the siting of proposed high‐voltage transmission lines, or other infrastructure, to limit effects on sandhill cranes and other avian species at risk of collision. Our approach can be replicated and applied in similar situations where birds are exposed to possible collision with power lines. © 2021 The Authors. The Journal of Wildlife Management published by Wiley Periodicals LLC on behalf of The Wildlife Society.